Relationship Between Serum Lactate Dehydrogenase Levels and Dengue Severity - Shahida Perveen,Hina Firdous, Muhammad Ali Khalid, Naseer Ahmed, Haider Zaigham Baqai (Journal of Rawalpindi Medical College, 2017)
To determine relationship between the levels of serum Lactate Dehydrogenase (LDH)on admission and prognosis of dengue fever. Methods: Patients (n=62) admitted with the diagnosis of dengue fever were included. On admission, serum LDH levels were measured in all patients and to find relationship we monitored all patients upto discharge. Monitoring was done for vitals, different blood parameters and duration of hospitalization. Results: Forty one (66.1%) were males and 33.9% (n=21) were females with mean age 31.73±13years.During hospital stay, 61.3% patients had Dengue fever (DF)while 39.7% patients developed dengue hemorrhagic fever (DHF).LDH levels were higher in patients with DHF(mean 618.38U/L±219)as compared to the patients with dengue fever (mean 316.45U/L±104).Mann Whitney U test showed the difference was statistically significant (p<0.001). Conclusion: Patients with early increase in serum LDH showed more complications as compared to low serum LDH level. High LDH can be used to predict outcome in dengue patients.